Essays in applied economics - Nieto Castro, Adrian (2019)
This thesis consists of two research articles. The first paper shows that permanent employment contracts are important drivers of the fertility decision. I provide causal evidence by using variation in subsidies to employers transforming temporary jobs into permanent in Spain as instrument for permanent employment. The amount of the subsidy markedly varies across regions, with the age and gender of the workers whose contract is converted, and within these three dimensions over time. Using a large administrative individual-level panel dataset, I show that permanent contracts have a positive impact on the fertility decision of men, but no effect for women. Several findings suggest that the effect declines when individuals are more likely to have a higher opportunity cost of having a child. I find that permanent employment has a lower impact on fertility when individuals are young, have a high wage growth, or do not cohabit with a partner. Based on a different regional level dataset, I replicate the findings from the main analysis and quantify the aggregate effects of the subsidies, which raised fertility by 2% at a cost of 13,300 euros per child. The second paper studies the impact of television on academic performance and educational inequality, and explores whether the previous effects depend on the educational value of the alternative activities that television crowds out. I identify a causal effect by using a natural experiment that consists in the staggered introduction of the digital television signal in the British television market. The digital switchover leads to an increase in the time that individuals watch television and a drop in the viewing shares of the traditional channels. I find that the digital switchover increases academic performance, contributing to human capital formation, and that the effect is larger in schools at the bottom of the scores distribution, reducing educational inequality. I also find that the digital switchover decreases the probability of children taking part in detrimental activities such as alcohol drinking, and their frequency. This suggests that the impact of television on education depends on the educational value of the out-of-school activities that television crowds out.